Multiple overlapping risk factors for childhood wheeze among children in Benin - IBIKOUNLE, MOUDACHIROU (My University, 2022)
Background: The African continent is currently facing an epidemiological transition characterized by a shift from communicable to non-communicable diseases. Prominent amongst the latter are allergies and asthma. In that con text, wheeze has multiple potential contributory factors that could include some of the endemic helminth infections, as well as environmental exposures, such as household air pollution. We sought to determine the relative importance of these risk factors among children in Benin. Methods: We included 964 children aged 6–14 years living in the commune of Comé, south–west Benin. All children were participants in the longitudinal monitoring cohort of the DeWorm3 trial designed to evaluate multiple rounds of community mass treatment with albendazole for interruption of the transmission of soil transmitted helminths (STH). We administered a standard ISAAC questionnaire to determine the presence of wheeze. In addition, we assessed exposure to household air pollution and to other potential allergy-inducing factors, dietary intake and anthropometry. Using STH infection status assessed at the pretreatment baseline timepoint, we used multivariate statistical modelling, controlling for covariates, to investigate associations between wheeze and the different factors measured. Results: The prevalence of wheezing history was 5.2%, of current wheezing was 4.6% and of severe wheezing was 3.1%, while STH infections were found in 5.6% of children. These profiles did not vary as a function of either age or gender. Infection with Ascaris lumbricoides, but not hookworm species, was significantly associated with both current wheeze (adjusted Odds Ratio (aOR) = 4.3; 95% CI [1.5–12.0]) and severe wheeze (aOR = 9.2; 95% CI [3.1–27.8]). Sig nificant positive associations with current wheeze, independent of each other and of STH infection status, were also found for (i) use of open cookstoves (aOR = 3.9; 95% CI [1.3–11.5]), (ii) use of palm cakes for fire lighting (aOR = 3.4; 95% CI [1.1–9.9]), (iii) contact with domestic animals and/or rodents (aOR = 2.5; 95% CI [1.1–6.0]), (iv) being overweight (aOR = 9.7; 95% CI [1.7–55.9]). Use of open cookstoves and being overweight were also independent risk factors for severe wheeze (aOR = 3.9; 95% CI [1.1–13.7]) and aOR = 10.3; 95% CI [1.8–60.0], respectively). Conclusions: Children infected with A. lumbricoides appear to be at elevated risk of wheeze. Deworming may be an important intervention to reduce these symptoms. Improving cooking methods to reduce household air pollution, modifying dietary habits to avoid overweight, and keeping animals out of the house are all additional measures that could also contribute to reducing childrens’ risk of wheeze. Policymakers in LMIC should consider tailoring public health measures to reflect the importance of these different risk factors
Keywords: Wheeze; Asthma; Air pollution; Open cookstoves; Ascaris infection